2019
DOI: 10.3390/jcm8111871
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancers in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: Results from the Korea National Health Insurance Claims Database 2010–2018

Abstract: The association between antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and cancer remains poorly understood. In this study, we searched the Korea National Health Insurance Claims Database to obtain data for 2097 AAV patients, and evaluated the risk of cancers in AAV. The standardized incidence ratios (SIRs) of overall and site-specific cancers were estimated in patients with AAV compared to the general population. The overall risk of cancer was significantly higher in patients with AAV (SIR 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 52 publications
0
18
2
Order By: Relevance
“…To identify SNV patients, the respective ICD-10 codes for MPA (M31.7), GPA (M31.3), EGPA (M30.1), and PAN (M30.0) were used. Patients were diagnosed with SNV when they were first registered with the corresponding ICD-10 codes for AAV or PAN in a general or tertiary hospital and were prescribed with glucocorticoids (betamethasone, dexamethasone, methylprednisolone, prednisone, prednisolone, hydrocortisone, triamcinolone, budesonide, and deflazacort) during the follow-up period ( 19 ). The date on which the diagnosis of SNV was first registered in the HIRA database was defined as the index date, and the medications of immunosuppressive agents (glucocorticoids, cyclophosphamide, rituximab, azathioprine/mizoribine, and methotrexate), antiplatelet agents (aspirin, clopidogrel), and statins that were prescribed after the diagnosis of SNV were also counted.…”
Section: Methodsmentioning
confidence: 99%
“…To identify SNV patients, the respective ICD-10 codes for MPA (M31.7), GPA (M31.3), EGPA (M30.1), and PAN (M30.0) were used. Patients were diagnosed with SNV when they were first registered with the corresponding ICD-10 codes for AAV or PAN in a general or tertiary hospital and were prescribed with glucocorticoids (betamethasone, dexamethasone, methylprednisolone, prednisone, prednisolone, hydrocortisone, triamcinolone, budesonide, and deflazacort) during the follow-up period ( 19 ). The date on which the diagnosis of SNV was first registered in the HIRA database was defined as the index date, and the medications of immunosuppressive agents (glucocorticoids, cyclophosphamide, rituximab, azathioprine/mizoribine, and methotrexate), antiplatelet agents (aspirin, clopidogrel), and statins that were prescribed after the diagnosis of SNV were also counted.…”
Section: Methodsmentioning
confidence: 99%
“…CYC therapy is also associated with increased risk of haematologic malignancies. In addition to significantly increased SIRs for lung cancer (SIR 2.32) and kidney cancer (SIR 5.01) in CYC‐treated SLE patients, Soo Ahn et al (2019) found increased SIR (SIR 13.82) for haematological cancer in these patients as well 23 . A retrospective case–control study (LoE 3b) of 75 SLE patients being treated with various immunosuppressive agents, including CYC, found patients who developed lymphoma had greater exposure to CYC therapy than other immunosuppressants 48 …”
Section: Resultsmentioning
confidence: 98%
“…Soo Ahn et al (2019) found that the overall cancer risk was significantly higher in these patients (SIR 1.90). Patients who were administered with combination AZA/mizoribine had a significantly higher risk of kidney cancer (SIR 5.46), haematological cancer (SIR 5.67) and “other remaining” cancers (SIR 3.25) which were coded by the researchers 23 . However, as these patients used both AZA and mizoribine are confounder and limit the conclusions that can made about the risk for malignancy in AZA alone.…”
Section: Resultsmentioning
confidence: 99%
“…We defined our patients as having SNV when they were diagnosed as AAV or PAN at a general or tertiary care hospital and were prescribed with glucocorticoids (methylprednisolone, hydrocortisone, prednisone, prednisolone, triamcinolone, budesonide, betamethasone, dexamethasone, or deflazacort) during the follow-up. To select SNV cases, the corresponding International Classification of Diseases (ICD)-10 codes for microscopic polyangiitis (MPA), granulomatosis with polyangiitis (GPA), eosinophilic granulomatosis with polyangiitis (EGPA), and PAN (M31.7, M31.3, M30.1, and M30.0, respectively) were used (20). Concerning the medications used by patients after the diagnosis of SNV and prior to the incidence of TB, the usage of glucocorticoids, cyclophosphamide, rituximab, azathioprine, and methotrexate was determined.…”
Section: Patient Selection and Data Extractionmentioning
confidence: 99%
“…On comparing the risk of TB according to 10-year age intervals, the risk of TB was significantly higher in all age groups of SNV, except for those aged 0-19 and 50-59 years. In particular, SIRs of TB were the highest in patients aged20-29 and 30-39 years (SIR 14.30, 95% CI 3.90-36.62; SIR 14.86, 95% CI 4.83-34.68). The risk of TB was equally high in patients with SNV regardless of sex (SIR 5.95, 95% CI 3.96-8.60 in men and SIR 6.26, 95% CI 3.97-9.39 in women).…”
mentioning
confidence: 97%